Halal Tourism as a Medium for Social Learning: The Role of Halal Certification and Muslim-Friendly Attributes in Strengthening Destination Image, Cultural Literacy, and Tourists' Visit Intention - Isdi Ahmad Delarean (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to explore how halal certification and Muslim-friendly attributes shape destination image and influence tourists' visit intention in Surakarta, while examining how halal tourism contributes to social learning, cultural education, and the strengthening of local identity through tourism experiences. Methodology: This study employed a qualitative case study approach. Data were collected through semi-structured interviews, field observations, and document analysis involving tourism managers, government representatives, tourism business operators, and tourists. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña with NVivo 12 software and validated through source triangulation, method triangulation, and member checking. Main Findings: The findings reveal that halal certification enhances tourists' trust by reducing uncertainty regarding tourism products and services, while Muslim-friendly attributes improve travel experiences and strengthen destination image. Beyond influencing visit intention, halal tourism also promotes social learning by increasing visitors' understanding of local cultural values, religious practices, and community traditions. The interaction between tourists and local communities contributes to cultural preservation, intercultural understanding, and the reinforcement of local identity within the tourism environment. Novelty/Originality of this study: This study extends halal tourism research by integrating Signaling Theory, Social Learning Theory, and Heritage Education to explain halal tourism as both a destination development strategy and a medium for social education. It demonstrates that halal certification and Muslim-friendly attributes not only enhance destination image and visit intention but also foster cultural literacy, strengthen local identity, encourage intercultural interaction, and support community-based learning in cultural tourism destinations.